Quantitative Easing In Overcoming the Crisis: Criticism ofQeinthe Monetary System Of Capitalism - et.al, Aang Kunaifi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to describe the form of Quantitative Easing applied by the Central Bank as well as qualitatively measure its benefits and excesses. To obtain a description and know the benefits and excesses in question, the research approach uses a qualitative approach by conducting a literature study of several facts and quantitative easing studies by Bank Indonesia and the Fed from various literature and media inductively relevant theories. This study's findings show that excesses can be detrimental to society, and countries that are shariah are harmful that should be avoided. This research is expected to encourage further research to determine the correlation of Quantitative Easing policy to the resolution of economic crisis and obtain alternative solutions by implementing the Islamic monetary system. The impact of the covid-19 pandemic that continues to this day causes economic shock, the slowing flow of goods commodities, decreased production, and decreased purchasing power of the community. Various policy efforts are carried out through fiscal stimulus as well as support through monetary policy in the form of quantitative easing.